2015
DOI: 10.1111/neup.12208
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal regional argyrophilic grain as a possible important factor affecting dementia in Parkinson's disease

Abstract: Argyrophilic grain (ArG) is the main pathological feature of argyrophilic grain disease (AGD) and is clinically characterized by cognitive impairment, behavioral abnormalities, personality changes, and emotional imbalances. However, ArG can not only be found in AGD but also in various other neurological disorders, including Parkinson's disease (PD). The association of ArG with psychosis and/or dementia in various neurological disorders remains unknown; in this study, we have investigated this in PD. The distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…When argyrophilic grain disease is found in a relatively restricted pathologic distribution involving limbic regions, the clinical phenotype is, again, often a slowly progressive pure amnestic syndrome that can also be seen in association with emotional and personality changes reflecting the limbic predominance of such pathology. 4,59,[63][64][65]72,73 Such distributions of argyrophilic grain disease pathology have also been seen in cases of Parkinson disease and are associated with an earlier onset of symptomatic psychotic features such as hallucinations, delusions, and paranoia. Yet other cases with profound behavioral, personality, and psychotic features that appear to exhibit the clinical phenotype of FTD have been shown to have more widespread cortical argyrophilic grain disease pathology in addition to the limbic predominance of this disease.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…When argyrophilic grain disease is found in a relatively restricted pathologic distribution involving limbic regions, the clinical phenotype is, again, often a slowly progressive pure amnestic syndrome that can also be seen in association with emotional and personality changes reflecting the limbic predominance of such pathology. 4,59,[63][64][65]72,73 Such distributions of argyrophilic grain disease pathology have also been seen in cases of Parkinson disease and are associated with an earlier onset of symptomatic psychotic features such as hallucinations, delusions, and paranoia. Yet other cases with profound behavioral, personality, and psychotic features that appear to exhibit the clinical phenotype of FTD have been shown to have more widespread cortical argyrophilic grain disease pathology in addition to the limbic predominance of this disease.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The influence of coexisting AGD in the development of cognitive impairment or psychiatric symptoms in LBD cases was examined in a few studies . Homma et al examined 20 cases of Parkinson’s disease (12 cases with dementia and eight cases without dementia), and demonstrated that five of 12 cases with dementia had severe AGD of Saito stage III. Of the eight cases without dementia, only one had AGD with Saito stage I.…”
Section: Pathological Relationship Between Agd and Lbdmentioning
confidence: 99%
“…Larger scale studies however are required to determine what, if any, role AGD pathology plays in patients with ALS who also exhibit dementia or cognitive decline. AGD pathology has also been found in cases of Alzheimer's disease, Parkinson's disease, Lewy body disease and even multiple system atrophy [9,14,19,20,43].…”
Section: Neuropathologymentioning
confidence: 99%
“…AGD was first described by Braak et al in 1987 as a progressive, late-onset neurodegenerative disease characterized by small spindle-or comma-shaped lesions in neuronal processes, referred to as argyrophilic grains, which can be highlighted by silver stains [7]. Neuropathologic changes of AGD may be found in isolation or in association with other neurodegenerative disorders such as Alzheimer's disease (AD), Pick's disease, progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), Parkinson's disease, and TDP-43 proteinopathies [14,19,20,37,38]. AGD has also been reported in association with dementia with Lewy bodies, Creutzfeldt-Jakob disease and multiple system atrophy, albeit rarely [11,43].…”
Section: Introductionmentioning
confidence: 99%